Catalytic Activity in Transfer Hydrogenation Using Ruthenium (Ii) Carbonyl Complexes Containing Two 1,8-Naphthyridine as N-Monodentate Ligands - Moya-Duran, S; Moya-Duran, S (Elsevier S.A., 2019)
A new series of novel complexes of type cis-[Ru(CO)2Cl2(L)2], L = 2-phenyl-1,8-naphthyridine, 2-(4′-nitrophenyl)-1,8-naphthyridine, 2-(4′-bromophenyl)-1,8-naphthyridine, 2-(4′-methylphenyl)-1,8-naphthyridine, 2-(3′-methoxyphenyl)-1,8-naphthyridine, 2-(2′-methoxyphenyl)-1,8-naphthyridine and 2-(4′-methoxyphenyl)-1,8-naphthyridine have been successfully synthesized and characterized. We found that the complexes can be directly synthesized from [RuCl2(CO)2]2 with high yield. The crystallographic structures of complex cis-[RuCl2(CO)2(2-(4′-methoxyphenyl)-1,8-naphthyridine-κN8)2] and cis-[RuCl2(CO)2(2-(2′-methoxyphenyl)-1,8-naphthyridine-κN8)2] have been established by X-ray single crystal diffraction studies, which indicate an octahedral geometry with two 1,8-naphthyridine ligands coordinated to the metal in a N-monodentate fashion. The ruthenium(II) complexes have been studied as catalysts in the transfer hydrogenation of acetophenone. We found that complexes show moderate activities and a 100% selectivity. The best turnover frequency (390 h−1) is found for cis-[RuCl2(CO)2(2-(4′-methoxyphenyl)-1,8-naphthyridine-κN8)2] when the substrate/catalysis ratio was 1000/1. The catalytic conditions were optimized using different substrate/catalyst and base/catalyst ratios. © 2018